A new Purkinje cell antibody (anti-Ca) associated with subacute cerebellar ataxia: immunological characterization - Jarius, Sven; Wandinger, Klaus P.; Horn, Sigrun; Heuer, Heike; Wildemann, Brigitte (Journal of neuroinflammation, 2010)
We report on a newly discovered serum and cerebrospinal fluid (CSF) reactivity to Purkinje cells (PCs) associated with subacute inflammatory cerebellar ataxia. The patient, a previously healthy 33-year-old lady, presented with severe limb and gait ataxia, dysarthria, and diplopia two weeks after she had recovered from a common cold. Immunohistochemical studies on mouse, rat, and monkey brain sections revealed binding of a high-titer (up to 1:10,000) IgG antibody to the cerebellar molecular layer, Purkinje cell (PC) layer, and white matter. The antibody is highly specific for PCs and binds to the cytoplasm as well as to the inner side of the membrane of PC somata, dendrites and axons. It is produced by B cell clones within the CNS, belongs to the IgG1 subclass, and activates complement in vitro. Western blotting of primate cerebellum extract revealed binding of CSF and serum IgG to an 80-97 kDa protein. Extensive control studies were performed to rule out a broad panel of previously described paraneoplastic and non-paraneoplastic antibodies known to be associated with cerebellar ataxia. Screening of >9000 human full length proteins by means of a protein array and additional confirmatory experiments revealed Rho GTPase activating protein 26 (ARHGAP26, GRAF, oligophrenin-1-like protein) as the target antigen. Preadsorption of the patient's serum with human ARHGAP26 but not preadsorption with other proteins resulted in complete loss of PC staining. Our findings suggest a role of autoimmunity against ARHGAP26 in the pathogenesis of subacute inflammatory cerebellar ataxia, and extend the panel of diagnostic markers for this devastating disease.